Synthesis and biological evaluation of simple carboxylated chalcone and aurone derivatives - Shauri, Thierry Lwanzo (Rhodes University, Faculty of Science, Department of Chemistry)
Restricted access. Expected release in 2026.
Keywords: Uncatalogued